The impact of physical activity on the psychosocial well-being of young employees - Achref Hasni; Hafsi Bedhioufi (Cogent Business & Management)
Psychosocial factors of well-being significantly impact employees’ professional environment, influencing businesses in many ways. This article investigates how physical activities can affect various aspects of young employees’ psychosocial well-being, specifically meaningful work, interpersonal relationships, and affective commitment. Focused on the demographics of young employees aged 18–35 in the Gafsa Mining Basin, our study surveyed a cohort of four hundred individuals to examine these psychosocial dimensions. Our analysis, employing independent samples t-test, reveals significant differences between physically active and inactive employees (p < 0.05). In terms of meaningful work, our findings underscore that engagement in physical activity is conducive to a heightened sense of purpose and fulfilment at work. Furthermore, involvement in physical activity substantially contributes to fostering positive interactions and strengthening harmonious workplace relationships. In addition, young employees who take part in physical activity prove to be more attached to their companies than those who do not. Our research highlights the imperative of promoting physical activity integration in professional milieu, positing that such initiatives can cultivate a more gratifying and productive work atmosphere.